(3GbJUGOjGJ GdGYeGd (B/s - (3GdTfhGfj, UdGMs ((3GdGScfOQjI(B: s (3TQcI LdGd ddWHGYI(B, s, 2000)
(3gPG GdcJGH gh ef EYOGO GdOcJhQ (B"(3UdGM GdTfhGfj(B" (3CSJGP EOGQI GdCYeGd GdeSGYO HcdjI GdJLGQI HLGeYI CSjhW hLGeYI HjQhJ GdYQHjI, hajg jJMOK Yf GdJMdjd GdGbJUGOj dfXQjGJ GdQHM hGdefGaSI hGdWdH hGdJcdaI hGdCSYGQ hZjQgG hPdc ef NdGd GYJeGOg Ydi GdWQb GdMOjKI aj GdGbJUGO GdQjGVj hHMhK GdShb, ceG hjQcR ef OQGSJg debQQ GbJUGOjGJ GdCYeGd Ydi Jdc GdfXQjGJ GdJj jecf bjGSgG hJWHjbgG aj GdeTGcd GdEOGQjI, ceG hQcR Ydi GdChLg GdQFjSjI abW ef GbJUGOjGJ GdeTQhY, hHGdGNJUGQ aEf GdeDda SjMGhd aj OQGSJg gPg EjLGO JcGed Hjf GdYOjO ef GdeHGOF hGdfXQjGJ ef ejGOjf eNJdaI, hef NdGd GdLhGfH GdJj dgG GJUGd HGdeTGcd GdNGUI HGJNGP GdbQGQGJ hQSe GdSjGSGJ Ydi eSJhi GdeTQhY, hSjchf ZQVg ef gPg GdOQGSI QaY caGjI GdeTQhY aj JMbjb CgOGag acGf YQVg cGdJGdj (B: 1- (3GdCQHGM (B2- (3GdefGaSI (B3- (3JYOO hJfhY GdSdY (B4- (3fXQjI GdWdH (B5- (3GdJcdaI (B6- (3fXQjI GdGSYGQ (B7- (3GJNGP GdbQGQGJ Ydi eSJhi GdGOGQI GdYdjGs
Keywords: (3GbJUGOjGJ GdCYeGds; (3GdJcdaIs; (3GdefGaSIs; (3SjGSGJ GdCQHGMs; (3fXQjI GdWdHs